2021
DOI: 10.1002/ame2.12193
|View full text |Cite
|
Sign up to set email alerts
|

Novel rat model of multiple mitochondrial dysfunction syndromes (MMDS) complicated with cardiomyopathy

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…The measurements were recorded as the average of at least three consecutive cardiac cycles. The LVDS, LVDD, LVPWS, LV posterior wall thickness at end diastole (LVPWD), SV, LVFS and LV mass were analyzed with Vevo LAB 5.5.0 ( Ling et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The measurements were recorded as the average of at least three consecutive cardiac cycles. The LVDS, LVDD, LVPWS, LV posterior wall thickness at end diastole (LVPWD), SV, LVFS and LV mass were analyzed with Vevo LAB 5.5.0 ( Ling et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ling et al developed a promising heterozygote knockout rat for the myocardium-specific Isca1 , a causal gene for multiple mitochondrial dysfunction syndromes with cardiac dysplasia [ 129 ]. From 3 months of age, rats manifest an echocardiographic and histopathological phenotype of DCM, characterized by LV wall thinning and dilatation, contractile impairment, myocardial lysis and fibrosis.…”
Section: Genetic Modelsmentioning
confidence: 99%
“…From 3 months of age, rats manifest an echocardiographic and histopathological phenotype of DCM, characterized by LV wall thinning and dilatation, contractile impairment, myocardial lysis and fibrosis. The subcellular mechanisms of mitochondrial dysfunction syndromes were clearly represented in this model, with swollen mitochondria containing damaged membrane structure and partial absence of crests, together with reduced expression levels of key enzymes for ATP synthesis and iron homeostasis [ 129 , 130 ].…”
Section: Genetic Modelsmentioning
confidence: 99%
“…Sayles et al reported that mutant CHCHD10 and/or CHCHD2 proteotoxicity activate the mitochondrial integrated stress response (ISR mt ), which causes profound metabolic imbalances, culminating in oxidative stress and iron dysregulation, and ultimately resulting in mitochondrial dysfunction and contributing to disease pathogenesis [ 28 , 29 ]. Recently, a myocardium-specific Isca1 knockout rat model of multiple mitochondrial dysfunction syndromes (MMDS) complicated with cardiomyopathy was applied to study the mechanism of energy metabolism in cardiovascular diseases, as well as for the development of drugs [ 30 ]. Nevertheless, the specific mechanisms that underlie cardiac developmental disorders are not yet well understood, and there is an urgent need for suitable in vivo animal models to aid research.…”
Section: Disease Modeling For MCMmentioning
confidence: 99%